the epistemics of presupposition projection - van Eijck, Jan; Unger, Christina (Proceedings of the Amsterdam Colloquium, 2007)
We carry out (formalize) the Karttunen-Stalnaker pragmatic account of presuppo sition projection within a state-of-the art version of dynamic epistemic logic. This sheds light on a recent controversy on the appropriateness of dynamic semantics as a tool for analysing presupposition.